Análise dos efeitos do tratamento preemptivo com terapia por fotobiomodulação a laser (660 nm) na viabilidade de retalho cutâneo em ratos - Martignago, Cintia Cristina Santi (2019)
Skin flap (SF) is a technique used in plastic surgery for many years to repair large lesions of the skin either due to trauma or after operative procedures, however, it presents as a complication tissue necrosis. A treatment that presentes scientific evidence for the reduction of SF necrosis is photobiomodulation therapy (TFBM). Due to the number of parameters involved in the dosimetry of this therapy, some gaps still exist in the literature. Thus the objectives of this work were; find the best site of application with the same irradiation time and investigate the effects of preemptive treatment associated with postoperative treatment with TFBM at different doses on viability in SF in rats. For this, 81 rats (Rattus norvegicus), males divided in two studies were used. In the first study, 18 animals were randomized into three groups. Group I (GI) simulation of TFBM, group II (GII) TFBM in three points in the cranial base of the SF and group III (GIII) TFBM in twelve points inside the SF. The animals of the GII presented smaller area of the necrosis and greater quantification of the collagen when compared with the control group. It was concluded that the application of the TFBM in three points in the cranial base of the SF was the most efficient. In the second study, 63 rats were randomized into five groups: Control Group (CG): TFBM simulation; Preemptive group + laser 1,1J (GP1): preemptive TFBM with 1.1J of energy per point; Preemptive group + laser 4J (GP4): preemptive TFBM with 4J of energy per point; Group 1 (G1): TFBM immediately after surgery with 1, 1J of energy per stitch, Group 4 (G4): TFBM immediately after surgery with 4J of energy per point, and on the third day after randomization the animals underwent cranial base SF surgery. The animals of GC, GP1 and GP4 had their treatments started 72 hours prior to surgery and were subdivided into 2 experimental periods, the first being on the day of SF. In the first evaluation it was possible to find a higher number of vessels, mast cells and greater expression of FGF and VEGF in GP1 compared to CG and higher expression of these same factors in GP4 compared to GC. In the second evaluation GP1 showed better results when compared to GC in the majority of analyzes. Thus, this study demonstrates that preemptive treatment with TFBM with the application of 1.1J of energy per point was effective in improving SF.